Pengaruh Kualitas Produk dan Online Customer Review Terhadap Keputusan Pembelian Produk Hand & Body Lotion Vaseline Gluta-Hya di Kota Surabaya - Ayu Pramesti, Aulia; Soebiantoro, Ugy; Mandasari, Virginia (Jurnal Riset Pendidikan Ekonomi, 2025)
Marketing plays a vital role in business success, where well-designed strategies such as high product quality and online customer reviews serve as a key determinants of consumer purchasing decisions. This study aims to examine the influence of product quality and online customer reviews on purchasing decisions for Vaseline Gluta-Hya hand & body lotion in Surabaya. A quantitative approach was employed, using purposive sampling with a total of 98 respondents. Data were analyzed using the PLS-SEM method with the assistance of SmartPLS version 4. The results show that both product quality and online customer reviews have a positive and significant effect on purchasing decisions. These findings indicate that consumers of Vaseline Gluta-Hya tend to choose products that offer tangible benefits and added value compared to competing products in the market. Moreover, online customer reviews serve as a crucial source of information for consumers in evaluating the product’s quality, strengths, and weaknesses.